(Re)pensar a interacção escola-família - Teresa Sarmento (Universidade do Minho, 2005)
The family in Portugal has always been a central value. In general terms, childrens education was almost granted by family unit. The socio-economicalcultural development produced multiple changes, which principally affected the familys structure level and education perspectives; it brought the problematic of education as a public action, to be promoted by the various educative agents. This passage from private worlds education to the public one had significant progresses but also backward steps, mainly because of the difficulties of each group to take certain position and the questions about advantages on educations continuity for children, parents and teachers. Hence the importance of the interaction between school-family gained space in different spheres, such as educative experiences, legislative terms or either in research development and scientific credibility. The aim of this article is to give a brief historical analysis about school-family interaction, gradually focused in some specific questions related to this topic, such as powers manage between elements which define themselves as co-workers: the institutional development and the participation of children in collaborative process. In this perspective, taking into account a scientific research developed in Instituto de Estudos da Criança (IEC) University of Minho, located in the field of childhood and primary education 1st. Level, we will try to present some of the main points that have been encountered and to raise new questions to reflect and act in this area.